Stable topical application of antimicrobials using plumbing rings in an ex vivo porcine corneal infection model - Daniel M. Foulkes; Keri Mclean; Tarunima Sharma; David G. Fernig; Stephen B. Kaye (PLoS ONE, 2025)
Microbial keratitis (MK) is a substantial cause of clinical blindness worldwide. Pseudomonas aeruginosa is an opportunistic Gram-negative bacterium and is the leading cause of MK. Infection models are vital tools in understanding host-pathogen interactions and the development of novel therapies. As well as ethical and practical advantages, ex vivo infection models enable researchers to study host-pathogen interactions with greater accuracy and physiological relevance compared to traditional cell culture systems. The versatility of porcine corneal ex vivo models have been employed to study various pathogens (for example Staphylococcus aureus and Acanthamoeba) and has enabled innovation of novel MK therapies. Here, we describe an improved porcine corneal ex vivo protocol, which uses plumbing rings and medical adhesive to circumvent several distinct limitations and challenges. The application of a 10 mm plumbing ring to the center of the cornea allows localized inoculation of pathogens of interest, maintaining them at the site of infection, rather than running the risk of “run off” of topically added aqueous solutions. The second important advantage is that topically applied therapeutic agents can be properly maintained on the cornea within the plumbing ring reservoir, allowing more accurate study of antimicrobial effects. In this contextualized protocol, we infected porcine corneas with the P. aeruginosa strain PA103 with topical treatments of moxifloxacin. PA103 colony-forming unit (CFU) quantification, spectrophotometric measurement of corneal opacity, and histological analysis of stromal edema using hematoxylin and eosin staining were employed to assess infection over 48 hours. Moxifloxacin treatment demonstrated a dose-dependent reduction in infection and corneal damage. These findings have contributed to the development of an improved and standardized ex vivo infection model for evaluating therapeutic interventions, potentially supporting clinical translation to alleviate the burden of microbial keratitis.